Microwave propagation on acupuncture channels. - Krevsky MA; Zinina ES; Koshurinov Y; Ovechkin AM; Tkachenko YA; Han W; Lee S; Yoon G (Acupuncture & Electro-Therapeutics Research, 2006)
Quantitative studies on functional state of acupuncture points and meridians have been done mostly by electrical measurement that requires the contact of the electrode on skin and is subject to pressure, humidity, etc. In this study, a new modality of using microwave was investigated. Microwave energy in the frequency range of 250 approximately 550MHz was irradiated on an acupuncture point. Transmitted microwave energy along the meridian was measured at the next acupuncture point of the same meridian. Diabetic and cancer patients were compared with healthy persons. Normal group consisted of 50 healthy persons. Diabetic group included 50 diabetic patients. Breast cancer group had also 50 patients. All 12 meridians on both right and left hands and feet were measured. For the diabetic group, the microwave energy propagation in this frequency range was 1.417 dB lower along Lung channel and 1.601 dB higher along Spleen channel compared with the normal group regardless of sex and diabetic types. For cancer patients, the propagation was 1.620 dB lower along Liver channel and 1.245 dB higher along Kidney channel compared with the normal group. Microwave energy proved to be a potential diagnostic method.